Reducing Stunting Through Mapping Convergence Interventions in Padang Pariaman Regency - ., Fatmawati; Dewata, Indang; U, Iswandi; Syah, Nurhasan; Barlian, Eri (Journal of Ecohumanism, 2025)
This research aims to reveal how to reduce stunting through mapping convergence interventions in Padang Pariaman Regency. This research used Mix Methods with a sequential explanatory design. Research targets focuses on families who give birth too young, too many, too close in spacing and too old. Families having no toilets for defecation and with inadequate water sources are as one of the target as well. The result shows; 1) Stunting are suffered from families with too many births, too close in spacing, and too young, 2) BKKBN conducted to outreach the families who give birth too old about the risks of giving birth, 3) BKKBN provided additional nutritional intake for pregnant women and children aged 6- 23 months, 4) BKKBN provided an assistance to poor and vulnerable families, 5) BKKBN campaigned to stop defecating in open area 6) a percentage of households that have access to adequate sanitation and adequate drinking water. Meanwhile, the types of treatment provided are 1) outreach to young women in consuming blood supplement tablets, 2) outreaching to mothers by socialization the importance of immunization and carrying out routine immunizations for children under five years, 3) Meal assistance for families who need it most 4) Ministry of Public Works prioritizes the vulnerable families to get adequate access drinking water and sanitation.